Tarekat Qadariyah Wa Naqsabandiyah: Implikasinya Terhadap Kesalehan Sosial - Firdaus, Firdaus (AL-ADYAN, 2017)
The Qoodiriyah Naqshbandiyah Tariqa is a combination of two large tariqas, the Tariqah Qadiriyah and the Naqshbandiyah Tariqa. The founder of this new tarekat was a great Sufi Sheikh who was then the Imam of the Al-Haram Mosque in Makkah al-Mukarramah, Shaykh Ahmad Khatib Ibn Abd. Ghaffar al-Sambasi al-Jawi (w.1878 AD). He is a great scholar of the archipelago who lived until the end of his life in Mecca. Shaykh Ahmad Khatib is a murshid of Tariqah Qadiriyah. Social piety is one of the important joints in Islam. Social piety is an application of one's muamalah which is a barometer of one's ritual piety level. The Qadiriyah Naqsabandiyah (TQN) Congregation is a religious social institution that also has a stake in realizing a minimum social piety program for its group. In this case, TQN synergizes both ritual and social piety to achieve the desirable khairu ummah.